‘Site of struggle’: The paradox of Black liberation theology - Joel Mokhoathi (HTS Teologiese Studies/Theological Studies)
The paradoxical nature of liberation theologies for African Christians has, for some time, been an intense subject of contestation. It has produced some polarised communities and made them acceptable on the basis of biblical interpretation. Liberation theological jargons such as ‘God sides with the poor’ and ‘God is for the oppressed’ seem to exemplify this attitude. As an acceptable standard of practice, this form of polarisation has been sustained through theological dogmas and ecclesiological dispositions. As a result, the South African biblical scholar, Itumeleng Mosala, has noted how the Bible is a ‘site of struggle’, which permits ideological contestations through biblical interpretation. His ideological formulations were later explored and expanded upon by Gerald O. West on ‘serving the sighs of the working class in South Africa with Marxist analysis of the Bible as a site of struggle’. This important work critically reflects on Itumeleng Mosala’s contribution to Black theology and its significance within the South African context. It considers Mosala’s use of Marxist concepts such as ‘mode of production’, his understanding of the relationship between biblical text and interpretive context and his ‘prophetic’ warnings about working with an ideologically uncontested Bible. It is to the latter – working with an ideologically uncontested Bible, that this paper is sorely focused.